Progressive Muscle Relaxation (PMR) Intervention with Slow Deep Breathing Exercise (SDBE) on Blood Pressure of Hypertension Patients - Sartika, Andry; Andri, Juli; Padila, Padila (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the difference between Intervention Effectiveness Progressive Muscle Relaxation (PMR) and Slow Deep Breathing Exercise (SDBE) in TD patients with hypertension. This type of research is an experimental design with a randomized pre-test and post-test three-group design without a control group. The results showed that there was a decrease in systolic and diastolic BP after the intervention in all groups. There was no significant difference in effectiveness between the three groups after the intervention; the optimal time to decrease systolic BP in the PMR and SDBE groups occurred on day 3. On the other hand, the diastolic BP does not show time. Optimal BP reduction. The conclusion of the three relaxation techniques effectively reduces blood pressure in patients with hypertension. Adequate time to lower blood pressure occurs on the third day. Keywords: Hypertension, Progressive Muscle Relaxation (PMR), Slow Deep Breathing Exercise (SDBE), Blood Pressure